Ocorrência de enteroparasitos em centros de educação infantil no Município de Patos de Minas, MG, Brasil - Silva, Luciana Pereira [UNESP]; Goncalves da Silva, Regildo Marcio [UNESP] (Universidade Federal de Uberlândia (UFU), 2010)
Considering the high prevalence of the parasitic diseases in Brazil and its close relationship with the socio-economic and cultural levels of the population, aimed to establish the occurrence of enteroparasites in children of six Centers of Education Child (CEIs) of the municipality of Patos of Minas (MG). Were collected three samples of faeces of 161 children from zero to six years of age. Were used the Lutz and Baermann-Moraes' methods, to the detection of cysts of protozoa, eggs and larvae of helminths. Coproparasitological analyses showed positivity of 73%. The most frequent helminths were: Ascaris lumbricoides (50%), hookworm (22%) and Enterobius vermicularis (0.6%). Among the protozoa highlighted were: Entamoeba histolytica/E. dispar (22%) and Giardia lamblia (32%). The high occurrence of enteroparasites evidenced the need for an effective health policy in the CEIs of the municipality of Patos of Minas to the fight against intestinal parasites.

Considerando a alta prevalência das doenças parasitárias no Brasil e sua estreita relação com o nível sócio-econômico e cultural da população, objetivou-se estabelecer a ocorrência de enteroparasitos em crianças de Centros de Educação Infantil (CEIs) do município de Patos de Minas (MG). Foram coletadas três amostras de fezes de 161 crianças entre zero a seis anos de idade. Utilizou-se os métodos de Lutz e Baermann-Moraes, visando à detecção de cistos de protozoários, ovos e larvas de helmintos. Exames coproparasitológicos realizados nas crianças de seis CEIs evidenciaram positividade de 73% para enteroparasitos. Os helmintos mais freqüentes foram: Ascaris lumbricoides (50%), Ancilostomídeos (22%) e Enterobius vermicularis (0,6%) e os protozoários foram: Entamoeba histolytica/E. dispar (22%) e Giardia lamblia (32%). Diante dos resultados obtidos, a elevada ocorrência de enteroparasitos evidenciou a necessidade de uma política sanitária, visando o combate às parasitoses intestinais e a aquisição de tratamentos específicos para a parasitose diagnosticada nas crianças contaminadas.
Occurrence of enteroparasites in centers education child of the municipality of Patos of Minas, MG, Brazil
Keywords: Enteroparasites; Children; Parasitism